2021
DOI: 10.3174/ajnr.a6942
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Treatment in Acute SAH with Hydrophilic-Coated Flow Diverters under Single-Antiplatelet Therapy: A 3-Center Experience

Abstract: BACKGROUND AND PURPOSE: In certain clinical circumstances, dual-antiplatelet therapy can be problematic in patients with acute SAH. In some aneurysms, however, flow-diverting stents are the ideal therapeutic option. We report our experience with ruptured intracranial aneurysms treated with flow diverters with hydrophilic coating (p48 MW HPC and p64 MW HPC) under single-antiplatelet therapy.MATERIALS AND METHODS: Patients were treated with either flow-diverter placement alone or a flow diverter and additional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The remaining 22 patients either recovered completely (n = 18) or regained independence in their daily routine (GOS 4: n = 4). In summary, high Hunt and Hess grades and the necessity for adjunctive techniques in ruptured dissecting VA aneurysms and respective comorbidities were associated with poor outcomes in our patients, according to earlier studies (11,17,30).…”
Section: Outcome-synopsissupporting
confidence: 75%
See 1 more Smart Citation
“…The remaining 22 patients either recovered completely (n = 18) or regained independence in their daily routine (GOS 4: n = 4). In summary, high Hunt and Hess grades and the necessity for adjunctive techniques in ruptured dissecting VA aneurysms and respective comorbidities were associated with poor outcomes in our patients, according to earlier studies (11,17,30).…”
Section: Outcome-synopsissupporting
confidence: 75%
“…However, several investigations suggested the feasibility and safety of this approach ( 25 , 29 ). Prior experience has shown that the hemorrhage-induced platelet activation requires a tailored dosage based on response tests (e.g., Multiplate, Roche Diagnostics; VerifyNow, Accriva), with prasugrel being more efficient than ASA ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stent-carrier module of the p64MW features an independently movable wire that can be placed 6 cm distal to the stent in order to provide increased stability during placement and preserve distal access after deployment. The potentially most significant improvement is its availability with a hydrophilic polymer coating that inhibits platelet adhesion and activation, and thus allows early reduction of DAPT or even single anti-platelet therapy (SAPT) (17,(22)(23)(24)(25)(26).…”
Section: The P64mw-hpc-featuresmentioning
confidence: 99%
“…Ex vivo testing has demonstrated that platelets in contact with HPC-covered FDS are significantly less activated than platelets in contact with uncoated FDS (16). Additionally, first clinical evidence indicates that applying the HPC technology to FDS allows reduction of DAPT in selected cases of unruptured and even ruptured cerebral aneurysms (17)(18)(19)(20). Whether the HPC technology may delay neo-endothelialization, and thus aneurysm occlusion, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Sufficient occlusion rates were also achieved for ruptured aneurysms, 2 even considering new techniques to address the issue of antithrombotic therapy in acute subarachnoid hemorrhage. 14,15 Concerning altered cerebral perfusion after implantation of a flow diverting device, risk factors include smoking and aneurysm size, 11 but late ischemic events seem to be rare. 7 In our case, the transient hypoperfusion of the A1 segment of the treated side was compensated by crossflow from the right ICA and normalized within twelve-month post-implantation.…”
Section: Discussionmentioning
confidence: 99%